The Impact of Social Capital on Crowdfunding Performance - Aprilia, Lady; Wibowo, Sigit S. (The South East Asian Journal of Management, 2017)
This study aims to analyze the effects of social capital—namely structural, relational, and cognitive dimensions—on crowdfunding performance using Kitabisa.com as a case study for 2013-2015. Using robust ordinary least squares methods, we find two important results. Structural dimension, which is measured by Facebook friends owned by an entrepreneur, affects crowdfunding success. The cognitive dimension, which is measured by the number of words that are written by entrepreneurs in the platform, also affects crowdfunding opportunities in order to wage a successful campaign. Using logistic regression technique, this study ﬁnds the same result, namely that the structural dimension and cognitive dimension have a positive relationship to the performance of crowdfunding. From a logistic regression, we can conclude that the number of Facebook friends and the amount of words to describe the project significantly positively influence the chances of success of the project; the more the number of friends and the number of words on a project, the greater chance of a project to achieve success. This study concludes Facebook friends owned by entrepreneur and number of words affect positively crowdfunding opportunities toward a successful campaign.